Improved piezoelectric properties of PLA/PZT hybrid composite films - Chakhchaoui, N; Frahan, R; Eddiai, A; Meddad, M; Cherkaoui, O; Boughaleb, Y; Van Langenhove, L (IOP conference series. Materials Science and Engineering, 2020)
Piezoelectric polymer-ceramic composites are promising materials for Sensing, Wireless electronics and actuating applications. We report the fabrication of highly piezoelectric biocompatible films containing lead zirconate titanate (PZT) ferroelectric ceramic particles dispersed in poly lactic acid (PLA) with different volume fractions using a solvent cast technique. The properties of the piezoelectric polymer-ceramic films were investigated by Fourier transform infrared spectrometry (FTIR) and field emission scanning electron microscopy (FE-SEM). In the FTIR spectra appear a large number of absorption bands which are attributed to the phases from PLA matrix confirming the total embedding of PZT filler into the matrix. The SEM results showed a good distribution of fillers in the matrix. We find that the added PZT imposes a significant effect on the α-β phase transformation. Our finding can lead to extraordinary enhancement of piezoelectric properties for the PLA/PZT composite films. Keywords: Piezoelectric polymer-ceramic, PLA, PZT, solvent cast technique.